Comparison of Flight Time Based on Jump Amplitude in the 540° Back-Turn Technique in Taekwondo: Técnica de giro hacia atrás en Taekwondo - Hye-Soo, Cho; Hong-Suk, Kim; Ji-Yong, Park; Soo-Kyung, Cho; Jin-Su, Eo (Revista Ecos de la Academia, 2025)
The study addressesed the need to optimize the teaching-learning process as well as the preparation to achieve performance in Taekwondo demonstrations, specifically in the 540° spinning back kick technique, by identifying the execution stages and the ideal amplitude of the jump to maximize the flight time and success rate. The main objective was to provide students, athletes and Taekwondo coaches with basic data on the methodological progression of the spinning back kick within the teaching process to improve the performance of taekwondists. The methodology used to assess the flight time in the execution of the phases of the kick technique according to the amplitude intervals of the jump was a repeated measures analysis of variance (ANOVA). For the success rate, the Friedman nonparametric analysis and the Wilcoxon test were used, with a statistical significance level of 0.05. The results showed that the P4 interval recorded the highest flight time in the execution phases of the kick technique, while the P3 interval obtained the highest success rate. However, combining both scores, since the differences between P3 and P4 were not statistically significant, it was concluded that P4 is the optimal interval since it represents the ideal amplitude of the jump to maximize both the flight time and the success rate in the 540° spinning back technique in Taekwondo, contributing to the preparation, learning and performance of the practitioners.
Keywords: biomechanics; learning; performance; Taekwondo; teaching